Development of Gamification-Based Smart Education Platforms to Increase Student Involvement - Syarif, Afwan; Som, Rit; Pao, Chai (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2025)
The integration of technology into education has led to innovative teaching methods aimed at enhancing student engagement and participation. One such method is gamification, which leverages game mechanics to make learning more interactive and motivating. However, traditional educational models often fail to fully engage students, resulting in disengagement and suboptimal learning outcomes. This study aims to develop a gamification-based smart education platform designed to increase student involvement by integrating game elements into the learning process. The primary objective is to assess the effectiveness of gamification in enhancing student engagement, learning outcomes, and overall classroom participation. A mixed-methods approach was used, combining both qualitative and quantitative data collection methods. The research involved the design, development, and implementation of a smart education platform that incorporated elements such as points, badges, leaderboards, and challenges. Data was gathered from 200 students across various disciplines, and engagement metrics, academic performance, and student feedback were analyzed. The results showed a significant increase in student involvement and motivation, with notable improvements in academic performance and class participation. Students reported a higher level of enjoyment and interaction with the platform, indicating that gamification enhanced their learning experience. This study concludes that gamification-based smart education platforms are an effective tool for increasing student engagement and improving learning outcomes, offering a promising approach for modern educational environments.